A construção do éthos na publicidade da Dove: uma oposição aos discursos intolerantes - Lorenz, Roseméri (2020)
A research object from classical antiquity – in Aristotle’s Rhetoric – many are the theories that still apply on the construction of ethos and pathos, includding the greimasian semiotics. Based on its assumptions, this thesis has as its main objective to understand and make explicit how and which enunciative mechanisms act on the tolerance ethos that emergesfrom the relationship between verbal and imagetic, in the printed advertising of Dove'shygiene and beauty products brand. Searching for the objective begins with the semiotics foundations presentation, indispensable for this research development, as the generative path of meaning and the syncretism notion, essential for the global understanding of texts that integrate verbal and non-verbal languages, such as advertising ones. In the sequence, we also discuss the notions of ethos and pathos, from Rhetoric to Discourse Analysis, clarifying how these notions were incorporated by discursive semiotics. The standards of beauty over the centuries are also addressed, the intolerant speeches that affect those who do not fit, the advertising text characteristics, especially Dove's brand advertisements. Then, as the lastand main step, the analysis of the corpus is carried out, consisting of three printed advertisements, published on "Boa Forma", "Contigo" and "Cláudia" magazines, in 2004, 2005 and 2016, respectively, which are part of the campaigns: "Real Beauty" and "Beauty out of the box". Systematizing the aspects to be observed in the texts, a analysis script is established, which begins with its content plan, following the generative path of meaning, from the reader's perspective, of the most superficial level to the deepest one. Thus, we proceed, in the first place, to identify the enunciative marks, syncretically present, at the discursive level of eachadvertisement, observing the effects of meaning produced, which contribute to the construction of the narrator's ethos. At narrative level, narrative program phases are verified, mainly manipulation form adopted, since the choice of the argumentative strategy is reflected in the narrator/enunciator identity; and the sanction phase, because its configuration is linked to the construction of (in)tolerant discourses. Finally, at the fundamental level, the aim is to define the semantic categories that are at the base of the text construction. As far as the plane of expression is concerned, the objective is to determine the categories corresponding to the topological, eidetic, photological and chromatic dimensions. These categories are then homologated to those of the content plane, as a way of "tying" the relations in a whole sense. The recurrences present in narrator's discourse on each of the texts make it possible to trace enunciator's ethos configuration: a tolerance ethos of diversity, welcome and respect for otherness. Such discourse, despite being a commercial strategy, contributes to promote the acceptance and social appreciation of differences.